Perbedaan Asupan Energi, Zat Gizi Makro dan Serat Berdasarkan Kadar Kolesterol Total pada Dewasa Muda Vegetarian di Indonesia Vegetarian Society Jakarta - Afrida Sukmawati; Laras Sitoayu; Yulia Wahyuni; Vira Herliana Putri (Jurnal Kesehatan Masyarakat Indonesia, 2021)
Background: Vegetarians are people who live from consuming plant-based (or plant-based) products with or without milk and eggs, but over all avoid eating meat, poultry and marine animals.. According to Household Health Survey (SKRT) cited Budiarti, in 2004 prevalence of hypercholesterolemia in Indonesia in the age range 25-65 years of 11.2%. One way to prevent elevated levels of cholesterol in the blood is to change the diet to become a vegetarian. Objective: To purpose the difference between energy intake, macro nutrients (protein, fat, and carbohydrates), fiber, based on total cholesterol levels in young vegetarian adults in Indonesia Vegetarian Society Jakarta. Methods: Cross sectional study design, independent Bed T-Test test if normal distribution data and Mann Whitney if the data is not normally distributed. Determination of the sample was done by means of different test of two mean and obtained sample of 70 people. Results: The results of the statistical test obtained p-value for energy intake, protein intake, fat intake, carbohydrate intake based on total cholesterol level with normal and abnormal category showed significant difference (p-value ≤ 0,05), and mean fiber intake showed no significant difference (p-value > 0,05). Conclusions: There are differences in energy, protein, fat, carbohydrate intake based on normal and abnormal total cholesterol levels, and fiber intake are expressed as no difference. There is a need for nutritional counseling and routine monitoring of total cholesterol in young vegetarian adults in IVS Jakarta.